2013
DOI: 10.1016/j.envexpbot.2012.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress response in Jatropha curcas: Growth and physiology

Abstract: a b s t r a c tTolerance to drought remains poorly described for Jatropha curcas accessions from different geographical and climatic origins. To address this issue we studied the response of two J. curcas accessions, one from Indonesia (wet tropical climate) and the other from Cape Verde islands (semi-arid climate). Potted seedlings (with 71 days) of both accessions were subjected to continuous well watered conditions (control) or to a drought stress period followed by re-watering. To mimic natural conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
92
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(125 citation statements)
references
References 52 publications
16
92
0
9
Order By: Relevance
“…As opposed to water loss reduction, stomatal closure also reduces the carbon assimilation, thereby causing reduced photosynthetic rate (Chaves et al, 2002). The positive relationship of variables A and E in comparison with gs, in J. curcas specimens subjected to drought and flooding treatments indicates that stomatal closure may be the major limiting factor of these variables (Cornic, 2000;Sapeta et al, 2013;Silva et al, 2010). This interaction between gs and E, shows the importance of controlling stomatal movement (opening and closing), in plants adapted to stress condition, as occured in J. curcas plants under water deficit, allowing the plant to maintain a high WUE (Naves- Barbiero et al, 2000;Yang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to water loss reduction, stomatal closure also reduces the carbon assimilation, thereby causing reduced photosynthetic rate (Chaves et al, 2002). The positive relationship of variables A and E in comparison with gs, in J. curcas specimens subjected to drought and flooding treatments indicates that stomatal closure may be the major limiting factor of these variables (Cornic, 2000;Sapeta et al, 2013;Silva et al, 2010). This interaction between gs and E, shows the importance of controlling stomatal movement (opening and closing), in plants adapted to stress condition, as occured in J. curcas plants under water deficit, allowing the plant to maintain a high WUE (Naves- Barbiero et al, 2000;Yang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…is an oilseed species, which, despite showing a strong capacity for survival and recovery from water stressed conditions (King et al, 2009;Wang et al, 2011;Verma et al, 2012), has shown negative responses to water deficit in reduced growth and biomass production (Fini et al, 2013;Sapeta et al, 2013). The attractive characteristics of J. curcas include its expected lifespan of 50 years and its broad climatic tolerance, covering zones with annual precipitation between 250 and 1200 mm (Achten et al, 2008).…”
Section: Jatropha Curcas L (Euphorbiaceae)mentioning
confidence: 99%
“…Nevertheless, in the case of J. curcas, this strategy still needs experimental verification. Succulence is a plant characteristic with clear ecophysiological implications (Mantovani, 1999;Mwine and Van Damme, 2011), which in J. curcas plants, until now, has been mainly explored in in relation to its adaptation to environments characterized by water deficit or soil salinity (Maes et al, 2009;Arcoverde et al, 2011;Díaz-López et al, 2012;Rodrigues et al, 2013;Sapeta et al, 2013).…”
Section: Resultsmentioning
confidence: 99%